The DIGITALISASI PERBANKAN TERHADAP KINERJA BANK : TINJAUAN SISTEMATIS DAN ANALISIS BIBLIOMETRIK - Husnaningtyas, Nadia (LP2M IBK Nitro, 2025)
Digital transformation has revolutionized global banking, enhancing efficiency, innovation, and customer experience. This study examines digital technology's impact on banking performance through a Systematic Literature Review (SLR) of 108 Scopus articles (2019–2025). Findings show digitally mature banks achieve 1.0–1.5% higher ROA, 10–15% lower cost-to-income ratios, and 15–25% fee-based revenue from digital services. Challenges include infrastructure gaps (40% rural areas lack internet), cyber risks (60–70% attack surge), and skill shortages (1.2 million professionals needed by 2025). Bibliometric analysis reveals three clusters: financial impacts, adoption drivers, and market-specific contexts (e.g., Islamic banking). The study offers an integrated impact model and practical transformation roadmap for banks.